1998
DOI: 10.1038/sj.bjc.6690035
|View full text |Cite
|
Sign up to set email alerts
|

Lack of DMBT1 expression in oesophageal, gastric and colon cancers

Abstract: Summary Loss of sequences from human chromosome 10q has been reported in several different cancers. Recently, a second candidate tumour-suppressor gene, DMBT1, was identified in this chromosomal region. We studied the mRNA expression and homozygous deletion of this gene in human oesophageal, gastric and colon cancers. Reverse transcriptase polymerase chain reaction (RT-PCR) amplification demonstrated that 23 (53.5%) of 43 oesophageal, 5 (12.5%) of 40 gastric, and 4 (16.7%) of 24 colorectal cancer cases showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 7 publications
5
76
1
Order By: Relevance
“…It is a glycoprotein containing multiple scavenger receptor cysteine-rich (SRCR) domains separated by SRCR-interspersed domains (SID) (Mollenhauer et al, 1997. Somatic alterations in genome structure affecting the DMBT1 gene region and loss of DMBT1 gene expression have been observed in glioblastomas, medulloblastomas (Mollenhauer et al, 1997) and in non-CNS tumors such as lung cancers (Takeshita et al, 1999;Wu et al, 1999) and GI tumors (Mori et al, 1999). In malignant astrocytic tumors further studies confirmed either hemizygous or homozygous alterations (Fujisawa et al, 1999;Sasaki et al, 2001;Somerville et al, 1998;Steck et al, 1999).…”
mentioning
confidence: 80%
“…It is a glycoprotein containing multiple scavenger receptor cysteine-rich (SRCR) domains separated by SRCR-interspersed domains (SID) (Mollenhauer et al, 1997. Somatic alterations in genome structure affecting the DMBT1 gene region and loss of DMBT1 gene expression have been observed in glioblastomas, medulloblastomas (Mollenhauer et al, 1997) and in non-CNS tumors such as lung cancers (Takeshita et al, 1999;Wu et al, 1999) and GI tumors (Mori et al, 1999). In malignant astrocytic tumors further studies confirmed either hemizygous or homozygous alterations (Fujisawa et al, 1999;Sasaki et al, 2001;Somerville et al, 1998;Steck et al, 1999).…”
mentioning
confidence: 80%
“…Lack of DMBT1 expression has also been reported in medulloblastoma and glioblastoma, 20 lung, 24 as well as esophageal, gastric and colon cancer. 25 The possible factors that cause lack of DMBT1 expression are still unclear. Somerville et al 22 suggested that homozygous loss at 74k STS, located at the N-terminal position of DMBT1, can be related with lack of DMBT1 expression because of its putative vicinity with the promoter.…”
Section: Discussionmentioning
confidence: 99%
“…4 Homozygous deletion has also been found in medulloblastoma, 20 oligodendroglioma, 23 lung cancer 24 and gastrointestinal cancer. 25 Although the function of this gene is not clear yet, the high frequency of deletions at the DMBT1 locus makes it to be one of the putative candidate tumor suppressor genes in chromosome 10.…”
mentioning
confidence: 99%
“…It was then proposed as a candidate tumor suppressor gene for lung and gastrointestinal tumors caused by homozygous deletions or by a lack of expression (Mori et al 1999, Wu et al 1999, Mollenhauer et al 2000. DMBT1 is involved in epithelial differentiation and mucosal innate immunity by binding to a large panel of pathogens including HIV (Mollenhauer et al 2000, Ligtenberg et al 2010, Madsen et al 2010, Al-Awqati 2011.…”
Section: Introductionmentioning
confidence: 99%